DIG-seq: a genome-wide CRISPR off-target profiling method using chromatin DNA - Kim, Daesik; Kim, Jin-Soo (Genome Research, 2018)
To investigate whether and how CRISPR-Cas9 on-target and off-target activities are affected by chromatin in eukaryotic cells, we first identified a series of identical endogenous DNA sequences present in both open and closed chromatin regions and then measured mutation frequencies at these sites in human cells using Cas9 complexed with matched or mismatched sgRNAs. Unlike matched sgRNAs, mismatched sgRNAs were highly sensitive to chromatin states, suggesting that off-target but not on-target DNA cleavage is hindered by chromatin. We next performed Digenome-seq using cell-free chromatin DNA (now termed DIG-seq) and histone-free genomic DNA in parallel and found that only a subset of sites, cleaved in histone-free DNA, were cut in chromatin DNA, suggesting that chromatin can inhibit Cas9 off-target effects in favor of its genome-wide specificity in cells.
10.1101/gr.236620.118